The Effect of Polymeric Flocculants on the Settling of Clinoptilolite Ion Exchange Material Used for Remediation of Nuclear Wastewater - Ojur, Jennet (Cranfield University, 2025)
Effective management of spent ion exchange (IEX) media is a critical challenge for nuclear wastewater remediation, particularly at Sellafield’s Site Ion Exchange Effluent Plant (SIXEP). The hydraulic transfer of clinoptilolite IEX material generates fine suspensions with poor settleability, high water content, and limited consolidation. This increases the storage demands and complicates downstream treatment. Polymeric flocculants offer a promising, low-cost solution; however, their performance is strongly influenced by molecular structure and operating conditions. This study evaluated the flocculation behaviour of two cationic polymers: a high-molecular-weight linear polyacrylamide (Flopam FO 4650 MPM, A1) and a branched polyamine-epichlorohydrin resin (Praestol DW31, A2) across solids concentrations of 0.1, 1, and 10 % (v/v) under normal and shear conditions. Flocculation performance was assessed through turbidity reduction, zeta potential, settled bed volume, polymer adsorption, floc size, fractal dimension, and microscopy. A1 consistently achieved superior clarification and formed more dense and compact flocs (Df ~2.8) through polymer bridging. These flocs presented stronger resilience to shear and achieved a regrowth capacity of ~50 %. In contrast, A2 operated primarily by patch flocculation, producing larger but fragile flocs (Df ~1.9) with a narrow effective dosage window and poorer shear resistance. These mechanistic differences present the importance of polymer architecture in governing both floc strength and operational robustness. Overall, Flopam FO 4650 MPM was the preferred flocculant for SIXEP sludges. The polymer demonstrated effective performance across a range of solids concentrations and operational conditions. Recommended dosages are 5 – 10 PPM for dilute suspensions, 10 – 15 PPM for medium solids, and 50 – 100 PPM for dense sludges. By linking polymer structure to settling efficiency and shear resilience, this work provides a framework for polymer selection in nuclear sludge treatment and contributes to the optimisation of flocculation strategies for long-term waste management.
Keywords: Spent ion exchange media; nuclear wastewater remediation; polymer flocculation; cationic flocculants; clinoptilolite sludge; SIXEP sludge treatment; flocculation mechanisms; shear resistance of flocs; settling and consolidation behaviour; nuclear waste management